AKTIVITAS ANTIMIKROBA EKSTRAK LIDAH BUAYA (ALOE BARBADENSIS MILLER) TERHADAP BAKTERI PATOGEN PADA IKAN - Dwi Hastuti, Sri (Jurnal Gamma, 2010)
?Streptocciacis? disease caused by streptococcus agalactiac has been attacked many tilapiafish farming, with the symptoms including abdominal bloating; bleeding in the eye, gill cover andbase of tail; become darker in color, and fast swmming fish unpalatable. Antibiotcs have been usedto over come this diseases, but the use of antibiotics continuously and unwisely can lead to bacterialresistence and impact on the envirotment, therefore alternative method for controlling the diseaseis important. this study was animed study was to detemine the antimicrobial activity of Aloebarbadensisi extract (saponin) toward S.agalactiae. Fresh Aloe barbandensis leaf washed thensterilized by using alcohol, dired in a preheated oven, then percolated and maserated by using nhexane and methanol for 24 hours. Then performed gravity column chromatography with a BEAdeveloper (Benzene Ethyl Acetate,Acetic acid with the ratio 75: 24: 1) on silica gel plates to ontainsaponin, then dried with a vacumm freeze dryer by using a dextrin as carrier agent, to from powder.MIC test and Inhibition zone test were performed to find the antimicrobial activity of sopaninextracted from Aloe barbadensis Miller, againt S.agalactiae. The result showed that the higher theconcentration of saponin extracted from Aloe barbadensis Miller, the better the atimicrobial activityagaint S.agalactiane. The highest of inhition zone found at concentration 12,5% with a doameterzone of 8.97 mm.